Variation linguistique perçue : quelques localités du Piémont occidental (Italie). Questions de méthodologie en dialectologie perceptuelle - Silvia Gally (Corela)
Although research conducted within the framework of Perceptual Dialectology (PD) varies considerably, its primary focus is on the study of speakers’ linguistic consciousness and linguistic awareness, in particular speakers’ perceptions of the language and language varieties that are spoken around them. For PD what the speakers perceive and think about the linguistic diatopic variation is as important as real speech productions. The aim of this field of study is to understand and to check a community’s sociolinguistic habits and to explain phenomena like linguistic variation and linguistic change. For these reasons, we present PD data collected in ten villages of the western Piedmont, in the northwest of Italy. We provide an analysis of our results inspired by the PD studies and its methodologies. Adopting this approach, we gathered a substantial amount of data as : a) descriptive data, in order to analyse the phonetic, lexical and morphological structures of linguistic varieties ; b) perceptual data on linguistic consciousness and awarenes like opinions, judgments, feelings, behaviours and attitudes.